Hyflex delivery mode in a postgraduate course: instructor and student perspectives - Therese M. Cumming; Lisa Gilanyi; Chen Han (Springer, 2024)
Abstract The global pandemic necessitated changes in the way university courses were delivered, forcing most teaching and learning online. Post-pandemic, many students continue to struggle with attending their classes on campus. It has been suggested that Hyflex delivery mode is a solution to this problem, allowing students to attend class either face to face or online, depending on their individual needs and preferences. There is, however, a dearth of literature focussed on whether the Hyflex model of course delivery is beneficial to students and feasible for instructors. This study explores the experiences and perspectives of both instructors and students of the HyFlex delivery mode in a postgraduate education course. The study employed a qualitative research design, using attendance records, surveys, and interviews to collect data from 11 students and two instructors. The findings suggested that HyFlex offers a flexible and adaptable approach to learning that can meet the diverse needs and preferences of students. Both instructors and students appreciated the flexibility and convenience of HyFlex, as well as the opportunities for engagement and interaction in both the face-to-face and online modes of delivery. However, the study also highlighted the challenges of HyFlex, particularly in relation to technology infrastructure and split instructor attention that could impact on self-efficacy. The authors provide recommendations for addressing these challenges and enhancing the benefits of HyFlex delivery mode. Overall, the study contributes to the growing body of research on HyFlex delivery mode and provides valuable insights for instructors using this mode of delivery in university courses.